OpenStreetMap Infrastructure Mapping and Its Usage on Flood Impact Assessment Using InaSAFE in Surabaya - Anjar Akrimullah; Biondi Sanda Sima; Yantisa Akhadi (Institut Teknologi Sepuluh Nopember, 2018)
OpenStreetMap has become one of the open data sources used for humanitarian purpose in the last decade. This paper focus on mapping process and flood impact assessment using InaSAFE on exposure data in Surabaya provided by OSM. Key infrastructure mapping by of one of the OSM groups HOT ID in Surabaya has provided various lessons and benefits for Surabaya. These lessons learned are very useful to improve the quality of OSM infrastructure data intrinsic quality and data management, particularly data that related to key and vulnerable infrastructure in the field of disaster risk reduction